Perencanaan Pengendalian Bahan Baku Pembuatan Standar Motor, Bastep Motor, dan Stang Motor (Studi Kasus: UD. X) - Rendragraha, Putra Riski; Mundari, Siti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research aims to develop a systematic raw material planning and control strategy for the production of three motorcycle components—center stands, footrests (bastep), and handlebars—at UD KS Pro, in order to minimize inventory costs and prevent both shortages and excess of raw materials. The company currently faces inefficiencies in managing raw materials, particularly iron pipes and iron plates, due to the absence of a structured planning method. This study employs a Material Requirement Planning (MRP) approach using historical demand data, the Master Production Schedule (MPS), and the Bill of Materials (BOM). The analysis process includes demand forecasting using the Moving Average method, calculating net material requirements, determining safety stock, reorder points, and lot sizing. The results show that implementing MRP helps the company optimize order quantities, reduce stock imbalance risks, and improve both cost efficiency and production continuity. This research is expected to serve as a reference for UD KS Pro in making more accurate and structured inventory management decisions.